Towards action-refinement in process algebras. - HENNESSY, MATTHEW (IEEE Computer Society Press., 1989)
A simple process algebra which supports a form of refinement of an action by a process is presented and the question of an appropriate equivalence relation for it is addressed. The main result is that an adequate equivalence can be defined in a very intuitive manner and moreover can be axiomatized in much the same way as the standard behavioral equivalences
PUBLISHED
Keywords: Administrative Staff Authors